Pemberdayaan Masyarakat Pesisir Galesong Utara melalui Pengelolaan Sampah Plastik: Pemberdayaan Masyarakat Pesisir Galesong Utara melalui Pengelolaan Sampah Plasti - humaerah, ST. aisyah; rahma, Nururrahmah (Jurnal Dialektika Politik, 2024)
The lack of community initiative in managing plastic waste due to the lack of local community knowledge has resulted in an increase in the accumulation of environmental waste in North Galesong marine waters. The increase in the amount of plastic waste is also caused by various activities carried out by communities around the coast. This research aims to provide an understanding regarding the empowerment of Galesong coastal communities in managing plastic waste. The methods used in community service activities (PKM) are qualitative methods in the form of observation, interviews, counseling and secondary socialization using an educational approach carried out in North Galesong District. The results of community service activities are increasing understanding and enthusiasm of residents in managing plastic waste into goods that can be sold through a container which can also increase the initiative capacity of coastal communities in improving environmental governance, especially plastic waste, namely through the waste bank unit which also plays a role. as additional income to meet the basic needs of coastal communities.